Pembentukan Citra Diri dalam Media Sosial Instagram: Kajian pada Mahasiswa Ilmu Komunikasi Universitas Trunojoyo Madura - Titis Adilia; Qoni'ah Nur Wijayani (Lembaga Pengembangan Kinerja Dosen, 2024)
Instagram as a social media has become a major platform for individuals to build their self-image online. This research aims to explore and analyze strategies for forming the self-image of Communication Science students at Trunojoyo University, Madura on the social media Instagram. Qualitative research methods were used to interview participants from Communication Science students who actively use Instagram. The research results show that students use various strategies, including photo selection, captions, filters, and hashtags, to build the desired self-image. They also manage interactions with followers and respond to comments to strengthen their self-image. Additionally, findings suggest that social pressure, cultural norms, and peer influence play an important role in the formation of self-image on social media. This research provides in-depth insight into how social media, especially Instagram, influences the formation of Communication Science students' self-image, and its implications for self-concept and social interactions in a digital context. This study also provides a foundation for the development of social media literacy among college students and stimulates further discussion about the impact of social media on individual identity construction.